(untitled) (Journal of Economic Research & Business Administration, 2017)
Development of small and medium-sized enterprise is the basis of any economy. The experience of developed countries shows that the creation and development of small and medium enterprise gives opportunity for economic recovery. Also it helps to form and develop a competitive environment and overcome sectoral and regional monopolies. Moreover, there is a saturation of the market in goods and service. It also can carry out de-monopolization of the economy. Furthermore, through developing technological progress, the tangible and intangible resources can be used effectively. Also, it can lead to increase export potential of country and it can be foster to format the middle classes, which is one of the key factor of sustainable development of country. These benefits contribute to the fact that small and medium enterprise is an essential element of the market economy, attractive to hundreds of thousands of people. This article examines the current condition of the small and medium enterprises in Kazakhstan and its competitiveness. In addition, there was described contribution of Kazakhstani small and medium enterprises to gross domestic product of the country. The weakest indicators in Kazakhstani small and medium enterprises development are low rate of real annual sale growth, low share of companies obtained international certification, low share of companies using websites, low percentages of companies investing in research and development activities. As the main obstacles of running business-high tax rates, corruption and access to finance were determined. In the conclusion were provided the suggestion for raising the level of competitiveness of Kazakhstani small and medium enterprises.